Analysis of Players’ Anxiety Level Before Futsal Matches in Futsal Extracurricular Activities at Public Elementary Schools Teluk Dalam 3 Banjarmasin - Taufik; Ramadhan Arifin; Lazuardy Akbar Fauzan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the level of anxiety of players, before a futsal match, in the futsal extracurricular, at Public Elementary Schools Teluk Dalam 3 Banjarmasin. The tool used in this study was a questionnaire, while the research method used was quantitative descriptive. Descriptive data analysis was carried out using percentages. The subjects in the study were extracurricular male futsal at Public Elementary Schools Teluk Dalam 3 Banjarmasin consisting of 17 students. The percentage results for the level of anxiety of players before a futsal match, in futsal extracurricular activities, at Public Elementary Schools Teluk Dalam 3 Banjarmasin, the number of intrinsic factors (originating from within the individual) consists of morale 13.92%, match experience 15.98%, negative thoughts 13.40%, complacent thoughts 15.98% with a percentage of 59.28%, and extrinsic factors (influenced by external environmental factors) consisting of coaches and teachers 15.98%, referees 4.64%, opponents 13.40%, friends and parents 6.70% with a percentage of 40.72%. The conclusion of this study shows that the most dominant level of anxiety in players before a futsal match at Public Elementary Schools Teluk Dalam 3 Banjarmasin is intrinsic anxiety compared to extrinsic.